USING DECODING SKILLS FOR STUDENTS AUTOMATICITY IN READING COMPREHENSION AT SMA NEGERI 10 MAROS: SMA Negeri 10 Maros - Kurniati; Syam, Ummi Khaerati; Sangkala , Ismail; Firman (English Language Teaching Methodology, 2023)
This study aims to determine whether there is a significant effect of using decoding skills on students' reading comprehension in grade X students of SMA Negeri 10 Maros in the academic year 2021-2022. The researcher applied a quasi-experimental design. In this study, the population was class X SMA Negeri 10 Maros with a total of 104 students from 4 classes, and the sample in this study was selected using a purposive sampling technique with a total of 52 students and divided into two classes: X MIA 1 as a control class that was treated without using decoding skills, and X MIA 2 as an experimental class that was treated using decoding skills. In this study, the method used was a quantitative one. The research instrument in this study used two reading tests that were administered twice: at the first meeting in learning, a pre-test was carried out, and at the last meeting in learning, a post-test was carried out after using decoding skills. The data was analysed using the t-test. The result obtained from this study showed the heterogeneity of student performance in reading comprehension after applying decoding skills and without applying the strategy. The result showed a post-test score p-value of 0,001 with a meaning rate of 0,05 (5%). In other words, the p-value (0,001) sig a = 0,05 (5%) was provided. Therefore, the outcome of the effect size was 1,58. It provided that using decoding skills was effective to use a strong level on students’ reading comprehension of descriptive text at the tenth-grade students of SMA Negeri 10 Maros at a strong level.